Listening Comprehension Problems Encountered by EFL Students at Coastal Area - Nainggolan, Elsa Ernawati; Hanifah, Hanifah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The study investigated listening comprehension problems of EFL students at coastal area, the strategies they used to solve the problems, and the learners’ view on learning listening with prior knowledge related content. To collect the data, 90 students taking the listening course on on-going semester participated by answering questionnaire which consist of 31 items. The results show that the students experienced listening problems on moderate level in all three cognitive processing related to perception problems, parsing problems, and utilization problems. This finding also indicate that the students have poor competency on the speech rate, clarity, vocabulary, and grammar structure. Meanwhile, to overcome these difficulties, the students prefer authentic listening audio and activities indicating ‘listening more to English songs’, ‘watching more English movie’, and ‘listening more to English classroom lectures’ on the highest demand. Reasonably, the EFL students at coastal area approve that listening to relevant knowledge content particularly marine life would support their comprehension. After all, considering content that links to students’ environmental context is necessarily noteworthy to support EFL students’ comprehension in listening.